Oligonucleotide Phosphorothioates Enter Cells by Thiol‐Mediated Uptake. (21st July 2021) - Laurent, Quentin; Martinent, Rémi; Moreau, Dimitri; Winssinger, Nicolas; Sakai, Naomi; Matile, Stefan
Abstract: Oligonucleotide phosphorothioates (OPS) are DNA or RNA mimics where one phosphate oxygen is replaced by a sulfur atom. They have been shown to enter mammalian cells much more efficiently than non‐modified DNA. Thus, solving one of the key challenges with oligonucleotide technology, OPS became very useful in practice, with several FDA‐approved drugs on the market or in late clinical trials. However, the mechanism accounting for this facile cellular uptake is unknown. Here, we show that OPS enter cells by thiol‐mediated uptake. The transient adaptive network produced by dynamic covalent pseudo‐disulfide exchange is characterized in action. Inhibitors with nanomolar efficiency are provided, together with activators that reduce endosomal capture for efficient delivery of OPS into the cytosol, the site of action. Abstract : Replacing one oxygen by one sulfur per monomer converts native oligonucleotides that cannot enter cells into cell‐penetrating oligophosphorothioates. The reason for this is thiol‐mediated uptake: dynamic covalent exchange with cellular thiols and disulfides that can be inhibited and activated according to the principles of dynamic covalent chemistry.